2000
DOI: 10.1063/1.870264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trailing jet instability on vortex ring formation

Abstract: Numerical simulations of an impulsively started jet were performed in order to investigate the effects of trailing jet instability on axisymmetric vortex ring formation. The predictions were compared to experimental results reported in the literature and to recently published numerical results. The total and vortex ring circulations were found to be in good agreement with both the experimental and the numerical results. The presence of a universal formation time scale was confirmed. The results also highlighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
59
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 12 publications
11
59
1
Order By: Relevance
“…The Reynolds numbers considered here are comparable with those observed in jetting swimmers such as paralarval and juvenile squid (O'Dor 1988; Bartol et al 2009) and several species of jellyfish (Gladfelter 1973;Colin & Costello 2002;Peng & Dabiri 2009), which have been observed to operate at Reynolds numbers in the range of 10 2 -10 3 . We did not consider the effects of varying the Reynolds number, since they have been previously characterized for circular vortex rings, and found to have little impact on the formation number, in the intermediate range of Reynolds numbers (Rosenfeld et al 1998;Mohseni et al 2000;Zhao et al 2000).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Reynolds numbers considered here are comparable with those observed in jetting swimmers such as paralarval and juvenile squid (O'Dor 1988; Bartol et al 2009) and several species of jellyfish (Gladfelter 1973;Colin & Costello 2002;Peng & Dabiri 2009), which have been observed to operate at Reynolds numbers in the range of 10 2 -10 3 . We did not consider the effects of varying the Reynolds number, since they have been previously characterized for circular vortex rings, and found to have little impact on the formation number, in the intermediate range of Reynolds numbers (Rosenfeld et al 1998;Mohseni et al 2000;Zhao et al 2000).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In particular, Rosenfeld et al (1998), Zhao, Frankel & Mongeau (2000) and Mohseni et al (2000), found the Reynolds number to have little impact on the formation number, provided that Re Γ is sufficiently large to ensure the formation process is completed before viscosity has a significant impact (Re Γ > 2000 according to Mohseni et al (2000)). The concept of the universal formation number has also been extended to more complex vortex generator setups and computational frameworks, by extending the definition of the dimensionless vortex formation time to allow for variations such as the presence of bulk coflow (Krueger et al 2006) or bulk counterflow (Dabiri & Gharib 2004a), a time-varying exit diameter (Mohseni et al 2000;Dabiri & Gharib 2005), and differing velocity programs (Rosenfeld et al 1998;Mohseni et al 2000;Krueger & Gharib 2003;Olcay & Krueger 2010) and velocity profiles (Rosenfeld et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…and U b (r, τ ) describes the radial dependence of the profile For the piston velocity program we used the model suggested by Zhao et al (2000):…”
Section: Physical and Numerical Parametersmentioning
confidence: 99%
“…Instabilities in the trailing jet can also affect the formation of the leading ring. Zhao et al (2000) found that trailing instabilities can accelerate detachment of the leading vortex thus reducing its final circulation and formation number.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies by Rosenfeld et al (1998) (hereafter, RRG) and Zhao et al (2000) have examined the parameters affecting the formation number for transient jets, finding a strong dependence on the velocity profile and a weak, but significant, dependence on the velocity program. Smoothing the velocity profile can decrease the formation number, while smooth accelerations can increase the value.…”
Section: Introductionmentioning
confidence: 99%